Scenario-Based Reflection for Integrated Early Childhood Education: A Qualitative Approach to Achieving Sustainable Development Goals (SDGs) - Sarah A. Alahmari; Moses Adeleke Adeoye (Bumi Publikasi Nusantara, 2026)
This study examines the use of scenario-based reflection as a qualitative approach to strengthening coordination in early childhood education and achieving Sustainable Development Goal (SDG) 4 on quality education. Through semi-structured interviews and reflective scenarios involving 48 participants (educators, caregivers, and policymakers), the research explored ethical reasoning and collaborative problem-solving within service integration. Findings reveal that participants gained deeper awareness of moral responsibility and professional accountability when confronted with realistic dilemmas, such as unequal resource allocation or family-school conflicts. One educator noted, “Reflecting on justice made me rethink fairness in daily teaching decisions.” Because reflection stimulates empathy and shared ethical understanding, scenario-based learning fosters stronger intersectoral trust and responsive decision-making. The study concludes that integrating faith-informed reflection, guided by Islamic principles of amanah (trust) and adl (justice), enhances both coordination and moral integrity in early education systems aligned with SDG 4.